Facilitators and Inhibitors of Collective Action: A Case Study of a US‐Owned Manufacturing Plant. (17th June 2013) - O'Sullivan, Michelle; Turner, Thomas
Abstract: This article develops a theoretical model of collective action at work using the key concepts of mobilization triggers, facilitating factors, and inhibiting factors. It then illustrates the value of this model for understanding why a low‐pay, low‐skill, blue‐collar manufacturing facility remained non‐union, drawing primarily on the accounts of a limited sample of redundant workers. These accounts are used to demonstrate the importance of social contexts where inhibiting conditions dominate and where management practices succeed in gaining worker consent and forestalling a collective response from workers.